Consistency of atterberg limit properties for crushed limestone aggregate base course between stockpile and in place material - Namathevan, Sreeramalu (2017)
This paper presents the test results and discuss the properties consistency for crushed limestone aggregate materials collected from the stockpile and from in-place after wetting, mixing, laying, grading and compacting on site using a 25 tonne roller compactor with a layer thickness of 300mm. A number of test was carried out to investigate the liquid limits and plasticity index properties of the crushed limestone. A total of 48 samples was collected, i.e. 24 samples from the stockpile and 24 samples from in-place. The samples collected from all the stockpiles i.e. from both Doha and Kuala Lumpur meets the ASTM D4318 test for plastic limits ranging from 22 to 25 and for the plasticity index (PI) ranging from non plastic to a maximum of 4. The results for the in place material samples showed an increase in values for both the Kuala Lumpur and Doha site in comparison to the results from the stockpiles with the plastic limits ranging from 23 to 35 and the plasticity index ranging from non plastic to 10. The results varied by location with the in-place samples from Kuala Lumpur complied with both the plastic and plasticity index limits while the inplace material results from Doha complied with the liquid limits but exceeded the plasticity index limit of 6. The results obtained and the observation made in this study suggests that limestone properties consistency varies with region, location and type of limestone with Kuala Lumpur limestone mainly consisting of composed crystallised carbonate rocks and formed marble rocks with minor intercalation of phyllite whereas the Doha limestone is overlain by younger strata that form a number of messa-type hills.